A giant congenital ranula: ignorance leading to feeding difficulties - Bachala, Keerthana; Bijay Kumar Suman; Ram Jeewan Singh; Shreyas Dudhani; Amit Kumar Sinha (International Journal of Contemporary Pediatrics, 2023)
The term “Ranula” originates from the Latin Word Rana which means “underbelly of a frog.” Ranula are epithelial retention cyst or mucus extravasation pseudo cyst arising from the sublingual glands. They are rare in children. A one-year-old female was brought to paediatric surgery emergency OPD by her mother with complaints of swelling arising from oral cavity since birth, gradually increased in size to attain current size. Mother also gives History of difficulty in feeding. Clinical examination revealed a large protruded tongue, with a cystic swelling in the floor of the mouth measuring around 6×4 cm, with elevation of the tongue. Child was further evaluated; ultrasound was suggestive of ranula. Marsupialisation of the cyst was done. Intraoperatively, cyst fluid was aspirated for analysis and cyst wall was opened and excised, lateral margins of cyst were sutured to base of mouth. Cyst fluid analysis revealed elevated amylase and normal LDH levels. The post-operative period was uneventful. The histopathology report showed a pattern consistent with ranula. Child was followed up for a period of 1 year and there was no evidence of recurrence. We report a case of giant congenital ranula. The rarity of this condition in children and its atypical size make this case report unique. We treated the child with marsupialization and there was no recurrence noted. Hereby I would like to state that congenital symptomatic ranulas though rare can be managed with marsupialisation.